A Shared Haplotype Indicates a Founder Event in Unverricht–Lundborg Disease Patients from Serbia. (1st February 2014) - Kecmanović, Miljana; Ristić, Aleksandar J.; Ercegovac, Marko; Keckarević-Marković, Milica; Keckarević, Dušan; Sokić, Dragoslav; Romac, Stanka
<x xml:space="preserve">Abstract</x> Unverricht–Lundborg disease (ULD) is an autosomal recessive disorder caused by dodecamer repeat expansion in the promoter region of the cystatin B (CSTB) gene in approximately 90% of the disease alleles worldwide. This study presents results of genetic findings in four Serbian unrelated patients with clinical and molecular diagnosis of ULD. Using newly established PCR protocol with betaine, we detected a homozygous expansion of dodecamer repeats in the CSTB gene in four patients with clinical diagnosis of ULD. Our results are in agreement with previous studies showing that dodecamer repeats expansion is the most common mutation associated with ULD. Haplotype analysis of eight unrelated ULD chromosomes was performed using seven markers flanking CSTB gene and one intragenic variant. We demonstrated the existence of a founder effect, strongly supported by LD calculations. Size of the minimal common haplotype implies that the most recent common ancestor of the Serbian ULD patients lived about 110 generations ago. We showed that Serbian ULD patients share the same common ancestor with patients from Baltic countries and North Africa. In the light of our data, we proposed extended minimal common haplotype, which could be considered as initial haplotype of the founder event common for Serbian, Baltic, and North African ULD patients.